A Method for the Automatic Generation of Test Suites from Object Models - Davies, J; Crichton, C; Cavarra, A (ACM, 2003)
This paper explains how object models written in the Unified Modeling Language (UML) can be translated into formal, behavioural descriptions and used as a basis for automatic test generation. The behavioural descriptions are written in a language of communicating state machines: the Intermediate Format (IF). The translation from UML to IF is based upon an earlier formal semantics, written in the Abstract State Machine (ASM) notation. Descriptions written in IF can be automatically explored; the results of these explorations are test trees, ready for input to a variety of testing packages.